AUDIT DELAY DAN FAKTOR – FAKTOR YANG MEMPENGARUHINYA (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2016 - 2019) - Faradila Bugis; Maslichah Maslichah; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted to analyze the effect of Profitability, Size of Public Accountants and Audit Committee on Audit Delay Case studies of Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2019. The sample used in this study is a manufacturing company sub-sector of the Consumer Goods Industry which is listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2019. Based on the test results in the previous chapter, it can be concluded that the simultaneous test results show that Profitability, Size of KAP and Committee Audit has a significant effect on Audit Delay in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. The partial test results show that Profitability has a significant negative effect on Audit Delay in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. Test results Partially shows that KAP size has a significant positive effect on Audit Delay in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2016-2019. Partial test results show that the Audit Committee has no significant effect on Audit Delay in Manufacturing Companies Listed on the Indonesia Stock Exchange 2016-2019.Keywords: Profitability, KAP Size, Audit Committee, Audit Delay